Peculiarities of suction, extraction and assignment of calcium in experimental chronic hepatitis in rats - Mogilevskaya, Tatiana; Makarenko, Olga; Khromagina, Larissa (ScienceRise: Biological Science, 2022)
The aim. Study the degree of absorption, assimilation, and excretion of calcium in rats with chronic toxic hepatitis. Materials and methods. The studies were carried out on 1 month old Wistar rats. Toxic hepatitis in the experimental group was reproduced by intraperitoneal injection of hydrazine sulfate at a dose of 50 mg / kg twice a week. Studies of the absorption of substances in rats were carried out under thiopental anesthesia according to the Tyri method after 3 months of pathology modelling. In the intestinal contents, the amount of unabsorbed calcium and amino acids was determined. To determine the amount of assimilated and excreted calcium metabolic chambers were used for daily collection of urine, faeces and food residues, in which the calcium content was determined (average for three days per animal). After removing the rats from the experiment, the level of calcium in the blood serum was determined, in the bone tissue – the degree of its resorption by the activity of acid phosphatase and the content of calcium. Results and discussion. Toxic hepatitis reduced calcium absorption by 34.5 % in the small intestine of rats and did not have a significant effect on amino acids, the inhibition of absorption of which in hepatitis was only 5.5 %. The excretion of calcium in the urine of rats with toxic hepatitis was reduced by 1.8 times, and with faeces, on the contrary, increased by 1.5 times. As a result, calcium absorption in rats with hepatitis decreased by 24.2 %. Decreased absorption of calcium, and its increased excretion in the faeces, led to a decrease in the level of this element in the blood of animals with hepatitis by 14.7 %. Our studies found bone destruction in rats with hepatitis: an increase in bone acid phosphatase activity by 65.3 % and a decrease in calcium levels by 15.5 %. Conclusion. The triggering mechanism for the development of hepatic osteodystrophy is the inhibition of calcium absorption in the small intestine of rats with hepatitis, consequently - a decrease in its absorption and level in the blood, which ultimately leads to the activation of bone resorption. The established patterns will form the basis of the pathogenetic scheme for the prevention of hepatic osteodystrophy